Functional Characterization of a Flavonoid Glycosyltransferase in Sweet Orange (Citrus sinensis) - Liu, Xiaogang; Lin, Cailing; Ma, Xiaodi; Tan, Yan; Wang, Jiuzhao; Zeng, Ming (Frontiers in Plant Science, 2018)
Fruits of sweet orange (Citrus sinensis), a popular commercial Citrus species, contains high concentrations of flavonoids beneficial to human health. These fruits predominantly accumulate O-glycosylated flavonoids, in which the disaccharides (neohesperidose (rhamnosyl-α-1,2-glucose) or rutinose (rhamnosyl-α-1,6-glucose)) are linked to the flavonoid aglycones through the 3- or 7-hydroxyl sites. The biotransformation of the flavonoid aglycones into O-rutinosides or O-neohesperidosides in the Citrus plants usually consists of two glycosylation reactions involving a series of uridine diphosphate (UDP)-sugar dependent glycosyltransferases (UGTs). Although several genes encoding flavonoid UGTs have been functionally characterized in the Citrus plants, full elucidation of the flavonoid glycosylation process remains elusive. Based on the available genomic and transcriptome data, we isolated a UGT with a high expression level in the sweet orange fruits that possibly encodes a flavonoid glucosyltransferase and/or rhamnosyltransferase. Biochemical analyses revealed that a broad range of flavonoid substrates could be glucosylated at their 3- and/or 7-hydrogen sites by the recombinant enzyme, including hesperetin, naringenin, diosmetin, quercetin, and kaempferol. Furthermore, overexpression of the gene could significantly increase the accumulation levels of quercetin 7-O-rhamnoside, quercetin 7-O-glucoside, and kaempferol 7-O-glucoside, implying that the enzyme has flavonoid 7-O-glucosyltransferase and 7-O-rhamnosyltransferase activities in vivo.